The Strategy and Effectiveness of Baitul Maal wa Tamwil in Eradicating Loan Shark Practices in Java and Sumatra - Jubaedah, Dedah; Sopiah, Evi; Fatahillah, Ikhwan Aulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of Baitul Maal wa Tamwil (BMT) as an Islamic microfinance institution in eliminating loan shark practices in communities, particularly in Java and Sumatra. Loan shark practices persist due to the ease and speed of loan disbursement, despite the high interest rates that entrap small communities in difficult-to-escape debt cycles. BMT offers a fair and interest-free Islamic financing solution based on profit-sharing principles and a more inclusive approach. This study discusses BMT’s financing strategies, such as lenient requirements, fast processing, and financial education programs designed to compete with loan sharks. The main findings indicate that BMT plays a significant role in providing fairer financing access to small communities and helping reduce their dependence on loan sharks. However, this study also reveals several challenges BMT faces, such as limited capital, strict regulations, and low financial literacy among the public. These challenges hinder BMT's ability to effectively compete with loan sharks in terms of speed and accessibility. The results of this study emphasize the importance of strengthening BMT’s capital, developing human resources, and innovating Islamic financing products so that BMT can play a more prominent role in eradicating loan shark practices in the community. With the right strategy and support from various stakeholders, BMT has great potential to continue growing as a more equitable and empowering financing solution.